Cultural Crowdfunding Platform Capitalism, Labour and Globalization - Rouzé, Vincent (University of Westminster Press, 2019)
"This new book analyses the strategies, usages and wider implications of crowdsourcing and crowdfunding platforms in the culture and communication industries that are reshaping economic, organizational and social logics. Platforms are the object of considerable hype with a growing global presence. Relying on individual contributions coordinated by social media to finance cultural production (and carry out promotional tasks) is a significant shift, especially when supported by morphing public policies, supposedly enhancing cultural diversity and accessibility. The aim of this book is to propose a critical analysis of these phenomena by questioning what follows from decisions to outsource modes of creation and funding to consumers. Drawing on research carried out within the 'Collab' programme backed by the French National Research Agency, the book considers how platforms are used to organize cultural labour and/or to control usages, following a logic of suggestion rather than overt injunction. Four key areas are considered: the history of crowdfunding as a system; whose interests crowdfunding may serve; the implications for digital labour and lastly crowdfunding's interface with globalization and contemporary capitalism. The book concludes with an assessment of claims that crowdfunding can democratize culture."